A harmony search-based memetic optimization model for integrated production and transportation scheduling in MTO manufacturing. (January 2017) - Guo, Zhaoxia; Shi, Leyuan; Chen, Longchao; Liang, Yong
Abstract: This paper investigates an integrated production and transportation scheduling problem in an MTO supply chain. A harmony search-based memetic optimization model is developed to handle this problem, in which certain heuristic procedures are proposed to convert the investigated problem into an order assignment problem. A novel improvisation process is also proposed to improve the optimum-seeking performance. The effectiveness of the proposed model is validated by numerical experiments. The experimental results show that (1) the proposed model can solve the investigated problem effectively and that (2) the proposed memetic optimization process exhibits better optimum-seeking performance than genetic algorithm-based and traditional memetic optimization processes. Highlights: We examine an integrated production and transportation scheduling (IPTS) problem. We use heuristic procedures to convert the IPTS problem into an order assignment problem. A harmony search-based memetic optimization model is proposed to handle this problem. A novel improvisation process for harmony search is proposed. The proposed optimization model has a very good optimum-seeking performance.